General practitioners' views on malnutrition management and oral nutritional supplementation prescription in the community: A qualitative study. (April 2020) - Dominguez Castro, Patricia; Reynolds, Ciara ME.; Kennelly, Sharon; Clyne, Barbara; Bury, Gerard; Hanlon, David; Murrin, Celine; McCullagh, Laura; Finnigan, Karen; Clarke, Sarah; Browne, Sarah; Perrotta, Carla; et al.
Summary: Background & aims: Malnutrition or undernutrition, arising from a deficiency of energy and protein intake, occurs commonly among community-dwelling individuals in developed countries. Once identified, malnutrition can be effectively treated in the majority of cases with dietary advice and the prescription of oral nutritional supplements (ONS) for patients who can eat and drink orally. However, previous research has reported inadequate screening and treatment of malnutrition in the community. The aim of this qualitative study was to explore general practitioners' (GPs) experiences and opinions on the management of malnutrition and the prescription of ONS in the primary care/community setting in Ireland. Methods: Sixteen semi-structured interviews including chart stimulated recalls (CSR) were conducted with GPs. The interviews and CSRs explored, among others, the following domains; barriers and facilitators in the management of malnutrition, ONS prescribing in the primary care/community setting, and future directions in the management of malnutrition and ONS prescribing. Recorded interviews were transcribed and analysed following a generic qualitative approach with inductive thematic analysis using NVIVO 12 to facilitate data management. Results: Three main themes were identified. Theme 1: 'Malnutrition is a secondary concern', encapsulating the idea that the identification of malnutrition is usually secondary to other clinical issues or disease rather than an independent clinical outcome. This theme also includes the idea that obesity is viewed as a dominant nutritional issue for GPs. Theme 2: 'Responsibility for malnutrition and ONS management in the community', highlighting that GPs feel they do not know who is responsible for the management of malnutrition in the community setting and expressed their need for more support from other healthcare professionals (HCPs) to effectively monitor and treat malnutrition. Theme 3: 'Reluctance to prescribe ONS', emerging from the GPs reported lack of knowledge to prescribe the appropriate ONS, their concern that ONS will replace the patient's meals and the costs associated with the prescription of ONS. Conclusions: GPs in Ireland do not routinely screen for malnutrition in their clinics as they feel unsupported in treating and managing malnutrition in the community due to limited or no dietetic service availability and time constraints. GPs also view malnutrition as a secondary concern to disease management and prioritise referral to dietetic services for patients with overweight and obesity. GPs reported that they have insufficient knowledge to change or discontinue ONS prescriptions. This study demonstrates that there is a clear need for primary care training in malnutrition identification, treatment and management and more community dietetic services are needed in order to support GPs and deliver high quality care to patients.